The Implementation of Ternate Mayor's Policy in Handling Household Waste in Kota Baru Village - Deni, Aji; Djamal, Yusuf; Husain, Thamrin; Saiful Deni; Darwin Abd Radjak (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to elaborate the implementation of the Ternate Mayor Regulation policy in handling Household Waste. The research uses a qualitative approach with Edward III's theoretical framework on the analysis of communication factors, sources, dispositions and bureaucratic structures on the stages of waste handling, namely collection, processing, collection and the final process of residents of Kota Baru Village, Central Ternate District, Ternate City. The findings of the dimensions of clarity, dimensions of consistency and transmission in handling household waste have not been fully socialized and do not touch the target group in the community, there are still limited budget resources, Transdepot waste facilities, the disposition has not been effective and efficient, and the bureaucratic structure has not functioned waste handling instruments in accordance with the Ternate Mayor Regulation, and lack of public awareness weak innovation and bureaucratic monitoring.